Surgery for extra-articular trismus: a systematic review. Issue 3 (April 2016) - Bouman, M.A.; Dijkstra, P.U.; Reintsema, H.; Roodenburg, J.L.N.; Werker, P.M.N.
Abstract: The aim of this systematic review was to identify operations that are used to improve mouth opening in patients with extra-articular trismus (caused by cancer and its treatment, oral submucous fibrosis, or noma) and to find out if they work. We searched the electronic databases PubMed, Embase, Cinahl, and the Cochrane collaboration, and then systematically selected papers before we assessed their quality, extracted the data, and did a meta-analysis. We analysed 32 studies that included 651 patients, the median (IQR) size of which was 11 (7-26). The quality of the methods used and of reporting were relatively low. Median (IQR) duration of follow-up was 12 (8-22) months. Operations resulted in a weighted mean (SD) increase in mouth opening of 19.3 (6.3) mm. None of the operations was better than the others for the improvement of mouth opening. We conclude that operations can improve mouth opening in extra-articular trismus, but the evidence is of moderate quality and there is a need for further research.